Adaptação às inundações urbanas em Rio do Sul, Santa Catarina - Murara, Pedro Germano (2016)
The floods is one of the main social problems that occurs in urban space. Knowing the vulnerability of the population affected by floods is fundamental for understanding actions that aim to mitigate the occurrence of this phenomenon. Therefore, to know this population, it is necessary to uncover what are the actions that individuals develop to protect themselves and adapt to recurrent episodes of floods. In this context, the present study aimed to analyze the vulnerability of the urban population of the Rio do Sul, located in the state of Santa Catarina. Based on the hypothesis that the population is not vulnerable to flooding, the thesis was supported by the adaptive capacity of individuals. The methodology involved data analysis of rainfall, flood records, mapping and identification of the vulnerability triad: exposure, sensitivity and adaptive capacity. Flood events affect the urban population differently, it is not entire urban population benefited from the financial resources after the emergency and calamity decrees. It was verified that the floods result from human actions in the production of the urban space and these are identified by their socionatural configuration. Therefore, vulnerability to flooding is constructed socially, not all individuals are exposed and vulnerable. The identification of elements and strategies that constitute actions that can be characterized as adaptive capacities of the population showed that these can constitute as an equalizer in the identification of vulnerability, however, the local population is in the process of adaptation more still vulnerable to recurrent episodes of flooding.